Gaining likes, but at what cost? Longitudinal relations between young adults' deceptive like-seeking on instagram, peer belonging and self-esteem. (November 2020) - Dumas, Tara M.; Maxwell-Smith, Matthew A.; Tremblay, Paul F.; Litt, Dana M.; Ellis, Wendy
Abstract: Social Networking Sites (SNSs) such as Instagram are a major part of the landscape of young adults' lives. SNSs are designed to encourage social connection and attention from others. However, deceptive like-seeking behaviors, which involve manipulative and deceitful acts to gain attention (e.g., buying followers, digitally modifying one's physical appearance in photos), are common on SNSs. The present study examined the relationship between deceptive like-seeking on Instagram, self-esteem and peer belonging using a longitudinal design. A total of 307 young adults ( M age  = 21.35 years, SD  = 1.50) completed two online surveys, 3 months apart. Rates of deceptive like-seeking and Instagram use and perceptions of self-esteem, peer belonging, and injunctive peer norms for deceptive like-seeking were collected. Path models were used to test hypotheses and determine pathways and moderators between variables at Time 1 and Time 2. Results showed that deceptive like-seeking predicted weakened feelings of peer belonging over time. Further, an interaction between self-esteem and injunctive peer norms demonstrated that only low self-esteem youth were susceptible to the effects of perceived peer norms; among these youth, those who perceived stronger peer approval increased in their deceptive like-seeking over time. These findings emphasize the dangers of dishonest online behavior for social relationships. Highlights: 63.5% of young adults had engaged in at least one deceptive behavior to gain Instagram likes. Deceptive like-seeking predicted weakened feelings of peer belonging across 3 months. Weaker feelings of peer belonging, however, did not predict changes in deceptive like-seeking. Deceptive like-seeking did not predict changes in self-esteem across 3 months. However, low self-esteem youth were significantly affected by peer norms for deceptive like-seeking.